Maresin 1 attenuates pro‐inflammatory activation induced by β‐amyloid and stimulates its uptake. Issue 1 (22nd November 2020) - Wang, Ying; Leppert, Axel; Tan, Shuai; van der Gaag, Bram; Li, Nailin; Schultzberg, Marianne; Hjorth, Erik
Abstract: Alzheimer's disease (AD) is the most common dementia, characterized by pathological accumulation of β‐amyloid (Aβ) and hyperphosphorylation of tau protein, together with a damaging chronic inflammation. The lack of effective treatments urgently warrants new therapeutic strategies. Resolution of inflammation, associated with beneficial and regenerative activities, is mediated by specialized pro‐resolving lipid mediators (SPMs) including maresin 1 (MaR1). Decreased levels of MaR1 have been observed in AD brains. However, the pro‐resolving role of MaR1 in AD has not been fully investigated. In the present study, human monocyte‐derived microglia (MdM) and a differentiated human monocyte cell line (THP‐1 cells) exposed to Aβ were used as models of AD neuroinflammation. We have studied the potential of MaR1 to inhibit pro‐inflammatory activation of Aβ and assessed its ability to stimulate phagocytosis of Aβ42 . MaR1 inhibited the Aβ42 ‐induced increase in cytokine secretion and stimulated the uptake of Aβ42 in both MdM and differentiated THP‐1 cells. MaR1 was also found to decrease chemokine secretion and reduce the associated increase in the activation marker CD40. Activation of kinases involved in transduction of inflammation was not affected by MaR1, but the activity of nuclear factor (NF)‐κB was decreased. Our data show that MaR1 exerts effects that indicate a pro‐resolving role in the context of AD and thus presents itself as a potential therapeutic target for AD.